The joint effects of partner rotation and allocation of audit hours on audit quality - Kang, Minjung; Kim, Sangil; Lee, Ho Young (Managerial Auditing Journal, 2023)
Purpose: This study aims to examine the effects of allocation of audit hours to year-round audits and audit partners on audit quality when a new partner is appointed. Design/methodology/approach: Using proprietary data of partners’ names and audit hours in the year-round context, the authors build a model testing input factors related to audit production and new partner assignment in 1,209 Korean listed firms during the period of 2015–2018. Findings: The results show that in the partner rotation, the more audit hours spent, the more audit hours are allocated to the year-round audit, or more nonpartners’ audit hours are allocated to the year-round audit, the higher the audit quality. Subsample analyses show that these findings are concentrated in firms with longer audit tenure or low audit risk. Research limitations/implications: The findings may provide regulatory authorities with practical guidelines concerning partner rotation and how to allocate audit hours to different audit stages and ranks (partner vs staff). Originality/value: To the best of the authors’ knowledge, this study provides the first evidence of the joint effects of partner rotation and audit hour allocation on audit quality.
Keywords: Audit hour allocation; Audit partner; Audit quality; Partner rotation; Year-end stage; Year-round stage